Upaya Peningkatan Pengetahuan Ibu Tentang Balita Sehat - Ni Putu, Aryani; Afrida, Bq. Ricca; Annisa, Nurul Hikmah; Idyawati, Susilia; Salfarina, Anna Layla; Zulviana, Yesvi; Herlina, Siskha Maya (Jurnal LENTERA, 2021)
The health and welfare of Indonesian children is far behind other countries. The Infant Mortality Rate has a downward trend, namely 97 per 1000 live births in the 1991 SKDI down to 40 per 1000 live births in the 2012 SKDI. The method of implementation in this activity includes the preparation, implementation and evaluation. In the preparatory stage, socialization is carried out to mothers of toddlers related to activities that will be carried out, namely counseling about healthy toddlers, asking for permission from related parties to prepare the place (village hall or meeting room) and preparing instruments and media for the implementation of activities. At the implementation stage, materials related to healthy toddlers are provided. At the evaluation stage, questions will be asked related to material about healthy toddlers. Counseling activities about healthy toddlers for mothers of toddlers in Batu Mekar Village, Lingsar District, West Lombok Regency, West Nusa Tenggara Province in 2020, will be held for one month, from 23 November to 11 December 2020, at 09.00 to finish in Batu Mekar Village, Lingsar District West Lombok Regency. The target of this activity is 30 mothers of toddlers. The form of the activity is providing material about healthy toddlers. Giving material about healthy toddlers for 30 minutes followed by a discussion. This activity includes education about healthy toddlers. Counseling and demonstrations are proven to be effective in increasing knowledge and skills about healthy toddlers in an effort to prevent pain in toddlers